IVABRADIN AND ATENOLOL EFFECTIVENESS COMPARISON IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY - P. Kh. Dzhanashiya; I. V. Markelova; N. S. Krylova; E. V. Avdeeva; V. A. Nazarenko; S. A. Nikolenko (Российский кардиологический журнал, 2010)
In 35 patients with hypertrophic cardiomyopathy, the effects of ivabradine (15 mg/d) and atenolol (50 mg/d) on physical stress tolerability (veloergometry test results) were investigated. Ivabradine and atenolol therapy was associated with increased test time: +1,5 minutes (p<0,01) and +2,4 minutes (p<0,01), respectively. Both medications prevented angina attacks and paradoxical blood pressure drop during the physical stress test.